Quality of life and unmet needs in patients with fabry disease: a qualitative study - Montserrat Morales; Jordi Cruz; Eduardo Brignani; Laura Acuña; Esther Lázaro; Cristina Soria (Orphanet Journal of Rare Diseases)
Abstract Background Patients with Fabry disease (FD) consider their quality of life to be significantly affected. The majority of studies evaluate the quality of life using quantitative measures and standardised scales that offer relevant information about experience with the disease in multiple aspects. The main objective of the research was to examine in depth the quality of life and unmet needs of patients diagnosed with FD in relation to their disease and treatment. A qualitative and transversal study was carried out in two stages: (a) nine semi-structured qualitative interviews with patients and one representative of the patient association, conducted individually by phone; (b) a focus group was set up with three patients diagnosed with FD and one relative. A deductive, thematic analysis approach was used for data coding and analysis. Results The analysis of the interviews revealed various relevant themes: experience with the disease, impact on daily activities, experience of the family and work environment, experience related to treatment and healthcare professionals, and unmet support needs. Diagnosis has a significant impact on both those suffering from the disease and on the family environment. The symptoms and evolution of the disease are highly variable among the patients interviewed and depend on the years diagnosed as well as the time taken to receive the diagnosis. The families of the interviewees have to go through an adjustment process in light of the significant psychological impact brought about by the disease. Patients show various unmet needs. The need mentioned most is to have more information, support, and understanding from people around them and society, improving empathy and raising awareness about the difficulties faced by people with FD while giving the disease visibility. A lack of social understanding is highlighted as one of the main challenges, as this does not only affect the emotional management of the disease but also has repercussions on working life and social relationships. Conclusions It seems necessary to define possible strategies that help to improve the quality of life of patients and their experience with the disease. Some recommendations obtained from the study include: facilitate access to mental health professionals for patients and their families; improve training for specialists and coordination among them; and carry out actions to raise awareness of the disease that are aimed at the general public, the patients themselves, and the people around them.